Contribution of Polymers to the Vegetative Propagation of Hypericum perforatum L. - GUNES, TOHIT; KEMAL AYAN, ALI; SAIT KURTAR, E.; HANDAN GUNES, M.; OZYUREK, CENGIZ (Asian Journal of Chemistry, 2010)
In present study, the contribution of two hydrophilic polymers to the vegetative propagation of Hypericum perforatum L.. has been investigated. Poly(acrylamide-g-ethylene diamine tetraacetic acid) polyelectrolyte hydrogels (AAm EDTA JEL4) and poly(N-vinyl-2-pyrrolidone/itaconic acid) (VPITA JEL4) polymers were used with seven different growth mediums. The seedlings were propagated with meristem tissue culture in Murashige and Skoog medium. The two polymers increased seedling survive and plant growth after transplantation. Polymers contributed to the vegetative propagation of Saint John's wort especially due to growth medium and increased survive of transplants. Growth mediums also effected the survive and growth rate of seedlings and contribution of polymers. When it thought that the secondary metabolites are found abundantly at early growth stages of young plants, this is an important contribution. The polymers contributed particularly in aridity.